PERKEMBANGAN MASA BAYI - Sabrina; Syajaro Tuddur; Sinta (CV. ALIM'SPUBLISHING, 2024)
Abstract. Language is a central part of human intelligence, it is important for us to understand how and when language is mastered as well as the social cognitive and neurological facts that influence language development at an early age. Language is a symbol system that is an important means of communication, even though we cannot communicate in other ways such as gestures, postures or facial expressions, language is our most flexible method of communication. Language allows us to describe the past and make plans for the future. Language allows us to convey traditional ideas and values to the next generation, thus language is of the most important cultural and social importance. Research using this method is carried out by comparing research methods, processing methods, and the results obtained from each article. The research source comes from articles obtained via the internet in the form of research articles discussing infancy development.The research results show. Speaking is a means of communication to be able to communicate with other people, all individuals must be able to master two different functions, the ability to grasp the meaning that other people want to communicate and the ability to communicate with other people in such a way that they can be understood. Early social experiences play an important role in determining future social relationships and patterns of behavior toward others. Learning to behave in a moral manner that is accepted by those around you is a long and slow process. But the basics are laid in infancy and it is based on these basics that babies develop moral codes that guide their behavior when they grow up.